Rhetoric as a Light to the Interpretation of the Quran - محمّدنبی احمدی; علی سلیمی (مطالعات زبانی و بلاغی)
In view of the fact that rhetoric refers to spirit of languages and discovers unseen aspects of texts, understanding of so many texts depends on rhetorical investigations. This is of more significance for commentators of the Quran, who have the task of interpretation of the Holy Book. Certainly, exegetists, who have neglected rhetorical themes like brevity, verbosity, metaphor, allegory, junction, disjunction, etc., could not catch heaven gifts of the Quran and failed to do their best. This paper tries to express the importance of this issue by giving some evidence from chapter 20 of the Quran (sura t{ÄhÄ)